Bibliometric Analysis of AI Technology Developments in Education: Trends, Collaborations, and Future Impact - Mayasari, Nanny; Niken Launingtia, I Gusti Ayu; Nanang, Nanang; Thamrin, Nur Sehang; A. Harbelubun, Y. Claudia Dhian (Westscience Press, 2024)
This study employs bibliometric analysis to explore the landscape of artificial intelligence (AI) applications in education. Through an extensive review of thematic clusters, research trends, author collaborations, and potential future research topics, the study maps the evolution and current state of AI in educational settings. Key findings indicate a robust focus on integrating AI within higher education and a significant emphasis on educational technology across various specialized domains. Temporal analysis reveals a progressive shift toward exploring advanced topics such as generative AI, reflecting the field's rapid adaptation to new technological advancements. Additionally, the author collaboration network illustrates a vibrant and interconnected academic community, while also identifying less explored areas like language education and AI in art education as promising fields for future research. The study highlights the dynamic nature of AI research in education, showcasing both the depth of current integrations and the potential for innovative applications that could further transform educational practices.